Insights from the relaunched Sweetpotato Knowledge Portal - International Potato Center (2016)
The Sweetpotato Knowledge Portal was relaunched on 15 February 2016. A comparison of the user statistics from the period 15 February-31 July 2016 against the same period in 2015 shows an upward trend in user engagement.